2004
DOI: 10.1080/1120009x.2004.11782393
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Thermal Ablation (RFA) of Liver Tumors: Open Surgical or Percutaneous Approach?

Abstract: RFA was used to ablate 81 liver lesions: 61 liver metastases and 20 hepatomas. An open surgical approach was adopted in 19 instances (27.5%), 12 of which were simultaneously treated for associated diseases, and percutaneous treatment was adopted in 50 instances (72.5%). The CT liver control at 6 months showed a complete necrosis in 50 lesions (66.3%). The advantages of the percutaneous approach include less invasiveness, reduced postoperative pain, shorter hospitalization, reduced costs and less discomfort in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Wagnetz et al, however, 27 reported that the sensitivities of multidetector computed tomography and MRI were equivalent or higher to that of IOUS in the identification of hepatic segments involved in hepatic malignancies, as well as having a higher predictive value for identifying tumor-free hepatic segments. This has been supported by other authors too [29][30][31] and hence it can be argued that though IOUS is a sensitive and accurate imaging technique for detection of focal lesions, particularly in colorectal metastases, multidetector CT (MDCT) and MRI yield similar results.…”
Section: Intraoperative Ultrasonographysupporting
confidence: 60%
“…Wagnetz et al, however, 27 reported that the sensitivities of multidetector computed tomography and MRI were equivalent or higher to that of IOUS in the identification of hepatic segments involved in hepatic malignancies, as well as having a higher predictive value for identifying tumor-free hepatic segments. This has been supported by other authors too [29][30][31] and hence it can be argued that though IOUS is a sensitive and accurate imaging technique for detection of focal lesions, particularly in colorectal metastases, multidetector CT (MDCT) and MRI yield similar results.…”
Section: Intraoperative Ultrasonographysupporting
confidence: 60%
“…Although reported to be a safe and accurate method [79], it is currently not routinely used in laparoscopic surgery [80], although the reliability of LIOUS in the staging of liver disease has been demonstrated to be similar to conventional IOUS [81]. Moreover, although many articles mention LIOUS as an important technique, few scientific papers described this technique [82][83][84][85].…”
Section: The Role Of Laparoscopic Approachmentioning
confidence: 99%
“…IOUS is a useful guidance tool in intraoperative diagnostic and therapeutic procedures [ 4 ]. Since IOUS provides excellent spatial resolution with a good sonic window and intraoperative procedures can be performed from various planes and angles that may shift over the course of an operation, IOUS guidance has clear advantages over transabdominal imaging guidance procedures with regard to accessibility, especially in procedures involving deeply located lesions or lesions hidden by overlying structures [ 5 , 63 , 64 ].…”
Section: Ious-guided Proceduresmentioning
confidence: 99%
“…These treatments are performed under imaging guidance, most frequently using either percutaneous ultrasonography or IOUS. While percutaneous tumor ablation has advantages including being less invasive, involving less postprocedure pain, and resulting in a shorter hospital stay, intraoperative ablation has advantages over percutaneous procedures because it allows better accessibility to all areas of the liver [ 64 , 70 ]. Therefore, laparoscopic or open surgical ablation can be an alternative treatment for liver tumors in locations that pose difficulties for the percutaneous approach, such as the caudate lobe [ 63 , 71 , 72 ].…”
Section: Ious-guided Proceduresmentioning
confidence: 99%